Design and development of downdraft gasifier to generate producer gas - Roslee, Darbi; Sabudin, Sulastri; Noor Ariffin, Nadhirah Aqilah; Jamari, Fathin Nadhirah; Mohideen Batcha, Mohd Faizal (Penerbit UTHM, 2018)
The drive towards renewable energy become intense nowadays due to the increasing price of fossil fuels and depletion of their sources. Among promising resource of renewable energy is the biomass. In Malaysia, oil palm biomass are available in large quantity and suitable for conversion into value added bio-fuels. In this study, an-innovative small-scale downdraft gasifier was designed, development and tested for biomass gasification. The gasifier operates at flowrate less than 0.1 m3/s with a capacity of 5 KW. During testing and commissioning of the gasifier, the maximum efficiency of the gasifier was found to be about 71% when firing empty fruit bunch pellets. This gasifier has potentials to be up scaled for actual use either for domestic or industrial use.